Clinoform identification and correlation in fine‐grained sediments: A case study using the Triassic Montney Formation. Issue 1 (18th September 2017) - Playter, Tiffany; Corlett, Hilary; Konhauser, Kurt; Robbins, Leslie; Rohais, SÉbastien; Crombez, Vincent; Maccormack, Kelsey; Rokosh, Dean; Prenoslo, Donald; Furlong, Carolyn M.; Pawlowicz, John; Gingras, Murray; et al.
Abstract: Stratigraphic correlation of fine‐grained successions is not always straightforward. Complicating factors, such as unconformities, structural complexity, subsidence and especially minimal grain‐size variation, make the application of traditional correlation methods to fine‐grained successions problematic. Alternatively, the analysis of detailed geochemical data can allow for the determination of variations in sediment provenance, mineralogy, detrital flux and hydrothermal input. When compared with modelled clay input over time, these geochemical indicators can be used to determine changes in relative sea‐level and palaeoclimate, allowing for the identification of clinoform surfaces. As an example, this study outlines detailed correlations of chemostratigraphic packages within the lower Triassic Montney Formation in Western Canada to demonstrate the effectiveness of chemostratigraphy in defining and correlating fine‐grained clinoforms across a sedimentary basin. The data set used includes five wells and one outcrop succession, from which geochemical profiles were generated and tied directly to mineralogical data and well logs. These analyses reveal 13 distinct chemostratigraphic packages that correlate across the basin. Observed elemental and inferred mineralogical changes highlight trends in relative sea‐level and palaeoclimate, as well as episodes of inferred hydrothermal input to the Montney basin. Cross‐plots of La/Sm and Yb/Sm further suggest hydrothermal input as well as the scavenging of middle rare earth elements by phosphatic fish debris. Additionally, plots of La/Sm versus Yb/Sm, which show volcanic arc input within the Doig Formation, suggest an additional sediment source from the west during the Anisian. Pairing detrital and clay proxies demonstrates changes in relative sea‐level and, at the Smithian/Spathian boundary, the lowest relative sea‐level in the Montney Formation is observed, corresponding to a change in climate.